Ocular Blood Flow and its Determination and Relevance in Glaucoma - Mahar, P. S. (Pakistan Journal of Ophthalmology, 2006)
Although intraocular pressure (IOP) is closely linked to the pathogenesis of primary open angle glaucoma (POAG) and reduction of IOP slows down the glaucoma damage, 12% of subjunctives with controlled IOP continue to have progressive visual field loss and about 30% of glaucoma patients never experience high IOP. Clinical existence of normotensive or low tension glaucoma confounds the traditional theory that elevated IOP is the only causative factor. Also various anti glaucoma drugs to lower IOP do not always prevent disease progress. Glaucoma may not be fully addressed by lowering IOP alone but also increasing the ocular perfusion dynamics by enhancing blood supply to the ocular tissues. Multiple techniques should be used to measure all relevant vascular beds in glaucoma such as Carotids, Choroidal circulation, retinal circulation and optic nerve head. We discuss usefulness of some techniques such as Color Doppler imaging, scanning laser ophthalmoscope (SLO) angiography, Heidelberg retinal flowmetry, Pulsatile ocular blood flow and Laser speckle tissue circulation analyzer to determine the ocular hemodynamics.